Penerapan Model Pembelajaran Example Non Example pada Pembelajaran Tematik - Nadya Yulianti Putri; Aswarliansyah Aswarliansyah; Nur Fitriyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the completion of the Thematic learning outcomes of third grade students at SD Negeri 43 Lubuklinggau. The research method used is in the form of a One Group Pretest-Posttest Design. The population is all grade III of SD Negeri 43 Lubuklinggau and at the same time the research sample is 25 students. Data collection was carried out using a test technique consisting of 17 questions with an average (78.82). The collected data were analyzed using the t-test. Based on the results of the t-test analysis with a significant level of α = 0.05, tcount (5.70) ≥ ttable (1.7108) Ha is accepted Ho is rejected, so it can be concluded that student learning outcomes after participating in Thematic learning using the Example Non Example model significant complete. Keywords: Example Non Example, Learning Outcomes, Thematic